The relationship of systemic inflammatory parameters with mortality and prognosis in patients with COVID-19 and acute ischemic stroke - Yilmaz Okuyan , Dilek; Karacan Golen , Meltem (Annals of Medical Research, 2022)
Aim: Inflammation plays a very important role in acute ischemic stroke (AIS) and many inflammatory markers are known to be associated with the prognosis of AIS. In this study, we aimed to evaluate the relationship of the systemic immune inflammation index (SII) and systemic inflammation response index (SIRI), which are two new inflammatory markers, with mortality and prognosis in patients with COVID-19 and AIS.Methods: Ninety-five patients with COVID-19 who were followed up for AIS were included in the study. SIRI and SII values were calculated using laboratory data  admission. The patients were divided into two groups according to prognosis and mortality. The modified Rankin scale (mRS) was used for prognosis at 3 months and mRS 0-2 was considered a good prognosis. Laboratory parameters neutrophil/lymphocyte ratio (NLR), SII, and SIRI values were compared between the groups according to prognosis and mortality.Results: The NLR, SII, and SIRI values ​​were found to be significantly higher in the poor prognosis group and the group with mortality (p
Keywords: COVID-19; stroke; SII; SIRI; prognosis; mortality